Decoding the Role of the Gatekeepers of Cyberspace in the Internet Economy: Analyzing the Legal Foundation of Intermediary Liability of Online Providers - Razon, Arvin Kristopher A. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
Introduction; I. Towards a Working Definition of Online Intermediaries; II. A Comparative Analysis of Intermediary Liability Under EU, US, and Philippine Law; III. The Economic Role of Online Intermediaries; IV. Shifting Gears: From a Regime of Intermediary Liability to Global Responsibility; V. Conclusion.
Keywords: Internet -- Law